Variasi Dialek dalam Penjualan Daring di Grup Facebook Jual Beli Apapun Sidoarjo - Ummi Maimunah; Fafi Inayatillah (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2026)
Facebook is an application that provides a platform for people to express themselves freely and communicate with anyone. Facebook is not only used as a communication medium, but can also be used as a platform to offer services or goods online. The data source for this study was obtained from the Facebook group "Jual Beli Beberapa Sidoarjo" in a post uploaded in November 2025. This study aims to describe the forms of dialect variation that occur in the "Jual Beli Beberapa Sidoarjo" group in terms of dialect. In this study, dialect variation was analyzed in the posts of sellers and buyers’ offers contained in the Facebook group "Jual Beli Beberapa Sidoarjo". This study used a qualitative descriptive method. Data collection used free listening techniques, note-taking techniques, and interview techniques. The data analysis process used descriptive analysis techniques adapted for sociolinguistic studies so that this study obtained results in the form of dialect variation data from the perspective of speakers. The results show that dialect variation is reflected through the use of regional language vocabulary in the Facebook group "Jual Beli Beberapa di Sidoarjo". Factors influencing language variation in this study include geography, speaker background, individual communication goals, and cultural similarities in digital communication.